2011
DOI: 10.1111/j.1365-2443.2011.01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Inner nuclear membrane protein Ima1 is dispensable for intranuclear positioning of centromeres

Abstract: Inner nuclear membrane (INM) proteins play a role in spatial organization of chromosomes within the nucleus. In the fission yeast Schizosaccharomyces pombe, Sad1, an INM protein of the conserved SUN-domain family, plays an active role in moving chromosomes along the nuclear membranes during meiotic prophase. Ima1 is another conserved INM protein recently identified. A previous study claimed that Ima1 is essential for mitotic cell growth, linking centromeric heterochromatin to the spindle-pole body. However, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 65 publications
4
88
0
Order By: Relevance
“…5B). Cut11 is a nuclear membrane protein whose ortholog, Ndc1, is a component of the nuclear pore complex (West et al 1998;Brohawn et al 2009), while Lem2 is an inner nuclear membrane protein (Hiraoka et al 2011). We found that Dsh1-13myc localized at the nuclear periphery but rarely colocalized with the Cut11 foci and tended to localize more proximal to nucleoplasm than Cut11 (Fig.…”
Section: Binding Of Rdrc To Heterochromatin Requires Dsh1mentioning
confidence: 69%
See 1 more Smart Citation
“…5B). Cut11 is a nuclear membrane protein whose ortholog, Ndc1, is a component of the nuclear pore complex (West et al 1998;Brohawn et al 2009), while Lem2 is an inner nuclear membrane protein (Hiraoka et al 2011). We found that Dsh1-13myc localized at the nuclear periphery but rarely colocalized with the Cut11 foci and tended to localize more proximal to nucleoplasm than Cut11 (Fig.…”
Section: Binding Of Rdrc To Heterochromatin Requires Dsh1mentioning
confidence: 69%
“…Since we observed one of the Dsh1 foci colocalized or closely localized with Cnp1 (Fig. 2D,E), and Lem2 was shown to localize to the spindle pole body (Hiraoka et al 2011), the colocalization of Dsh1 and Lem2 appeared to occur at the spindle pole body, where centromeric heterochromatin clustered.…”
Section: Binding Of Rdrc To Heterochromatin Requires Dsh1mentioning
confidence: 99%
“…This verifies IF data that show that Ima1 specifically binds to heterochromatic regions. However, Ima1 is dispensable for the tethering of centromeric DNA to the SPB region of the nuclear periphery (King et al 2008;Hiraoka et al 2011). Rather, the Ima1-interacting loci are enriched with the RNAi components, Dcr1 and Rdp1.…”
Section: Nuclear Organization In S Pombementioning
confidence: 99%
“…), which could explain the partial suppression of the silencing defect in these double mutants. In conclusion, whereas Lem2, Man1, and Ima1 may have overlapping roles in other pathways (Hiraoka et al 2011), heterochromatic silencing is exclusively mediated by Lem2.…”
Section: Ura4mentioning
confidence: 99%
“…Two INM proteins, Man1 and Ima1, have been reported to have overlapping functions with Lem2 in ensuring nuclear membrane integrity (Hiraoka et al 2011). In addition, Man1 was shown to associate with subtelomeric regions (Steglich et al 2012), which may suggest a role in telomeric silencing.…”
Section: Ura4mentioning
confidence: 99%